"A thing one knows not how to name:" the female grotesque in early modern English drama - Seval, Ayşem. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2008., 2008)
Deriving from the ambivalence inherent in the concept of the grotesque, this dissertation aims to investigate how the female grotesque may offer possibilities for problematising stereotypical images of women as fools or the fickle incarnations of the devil even when it is employed in Tudor and Stuart Drama as crowd-pleasing and profit-increasing spectacle. Contrary to the arguments of some of the feminist critics, this study argues that the concept of the female grotesque may suggest cultural politics for women not just in the works of some twentieth-century female writers but even in a male-dominated genre such as the early modern English drama. After having discussed the different types of the grotesque and the social and historical background to the various female grotesque images such as the monster, the witch and the Amazon, the dissertation illustrates how, in Tudor and Stuart drama, these female grotesque images offer more than a simplified one-dimensional misogynist myth on women by exposing and questioning the complex web of power relations involved in their creation.
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism.; Grotesque -- Great Britain -- History.; Grotesque in literature.